2022
DOI: 10.3390/jcm11071967
|View full text |Cite
|
Sign up to set email alerts
|

Management and Long-Term Follow-Up of Hyperparathyroidism in Multiple Endocrine Neoplasia Type 1: Single Center Experience

Abstract: Background: Primary hyperparathyroidism (PHPT) in the most common and earliest manifestation of multiple endocrine neoplasia type-1 (MEN1). Epidemiological data have been reported in MEN1 patients but data on long-term follow-up focusing on PHPT are scarce. Methods: In this retrospective cohort study, we included patients diagnosed with MEN1-related PHPT that were under regular follow-up in our institution. Results: Data on 68 patients (39 males), with a mean age at MEN1-diagnosis of 39 ± 13.06 years, were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The studies' overview (n = 7) showed cohorts that primarily included patients with MEN1-related insulinomas (n = 2) or MEN1-associated primary hyperparathyroidism (n = 2) or analyses of genetic testing in MEN1 (n = 3), a wide spectrum of objectives being registered across these data. They were all retrospective studies enrolling between 17 and 517 individuals per study, for a total of 877 MEN1 subjects [109][110][111][112][113][114][115] (Table 5). PHP with single-gland involvement: 47% (N1) versus 0% (N2)…”
Section: B Clinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies' overview (n = 7) showed cohorts that primarily included patients with MEN1-related insulinomas (n = 2) or MEN1-associated primary hyperparathyroidism (n = 2) or analyses of genetic testing in MEN1 (n = 3), a wide spectrum of objectives being registered across these data. They were all retrospective studies enrolling between 17 and 517 individuals per study, for a total of 877 MEN1 subjects [109][110][111][112][113][114][115] (Table 5). PHP with single-gland involvement: 47% (N1) versus 0% (N2)…”
Section: B Clinical Studiesmentioning
confidence: 99%
“…MEN1-associated parathyroid NETs (N = 585), as the most common and usually the first clinical element in MEN1, were meticulously addressed from the surgical perspective and post-parathyroidectomy outcome since this step of management is essential for an overall better prognosis. For instance, Yavropoulou et al [ 112 ] showed in 68 patients with MEN1-related primary hyperparathyroidism that the average age at syndrome recognition was 39 ± 13.06 years and at parathyroid condition confirmation, 35.2 ± 4 years. The surgical outcome for those 82% of subjects who underwent parathyroidectomy included the following: long-term remission (56%), recurrent hyperparathyroidism (31.5%), persistent hyperparathyroidism (12.2%), and permanent hypoparathyroidism (19.2%) for a 4-year median follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations